Social innovation of Kampung Kopi Luwak Prangat Baru Village (Kapak Prabu) East Borneo - Muhammad Busyairi; Abdul Kahar; Akhmad Rafii; Dharma Saputra; Asih Soenarih; Vivi Apriliyani; Dita Aprilia; Muthia Andriani; Aulia Miftahul Jannah (Community Empowerment, 2023)
Prangat Baru Village is located in a hilly area, with rainfall of 194.5 and an altitude of 150 meters above sea level. The majority of the community work as garden farmers. Farmers are encouraged to innovate in search of other plantation crop commodities, namely the cultivation of liberika coffee plants by naturally fermenting coffee beans by civets. The main objective of this program is to increase the economic level of the members of the Kopi Luwak Village farmer group through 3 (three) basic foundations, namely (1) liberika coffee cultivation, (2) civet care which pays attention to animal welfare, and (3) edutour of Kampung Kopi Luwak with various educational tourism activities. Through deliberations on the preparation of the 2021 Renja with the management of Pertamina Hulu East Borneo, it was agreed upon the activities of the Kapak Prabu 2021. Among them are a comparative study of coffee cultivation in Pangalengan Malabar, West Java, assistance for PIRT powder & coffee beans with more marketable packaging, procurement and development of liberika coffee seeds, as well as the addition of cages and pandanus civet. Based on the results of the implementation of assistance in the kapak prabu social innovation program, the basic problems of the Prangat Baru Village community were resolved and the need for social innovation had been properly achieved.